Model of Public Policy Implementation for Refused Derived Fuel (RDF) Waste Management in Cilacap Regency - Syamsul Auliya Rachman; Muchlis Hamdi; Aries Djaenuri; Ika Sartika (GoAcademica Research & Publishing, 2020)
The problem of waste management in big cities worldwide and especially Indonesia, has become an ongoing issue. Every country globally competes in developing various technologies in waste management, such as sanitary landfills, incineration, gasification, and anaerobic digestion technology. This study intends to describe the right model for waste management, especially for areas in Indonesia. In this case, the writer tries to discuss waste management innovation in Cilacap Regency by using a waste management policy implementation model with Refused Derived Fuel (RDF) technology, which converts waste into alternative fuel to replace coal. In this paper, the writer tries to analyze it with a descriptive design with a qualitative approach. Writing informants were determined by purposive sampling. The results of this study, according to the author, indicate that the implementation of RDF public policy on waste management can be carried out with several approaches, namely: (1) RDF Waste Management Policy Model with a Collaborative Waste Management Service approach; (2) RDF Waste Management Policy Model with the Buy and Sell Cooperation approach of RDF results; (3) RDF Waste Management Policy Model with a Joint Venture (JO) approach; (4) RDF waste management policy model with an Operational Cooperation approach with the presence of foreign assistance, the central government and provincial governments; (5) RDF waste management policy model with the formation of regional companies.